INTELLECTUAL CAPITAL AND ITS IMPACT ON FINANCIAL PROFITABILITY AND INVESTORS’ CAPITAL GAIN ON SHARES - Basuki Basuki; Mutiara Sianipar (Journal of Economics, Business, and Accountancy Ventura, 2012)
The research attempts to investigate the influence of efficiency of value added by the majorcomponents of a firm’s resource base (physical capital, human capital, and structural capital)towards financial profitability (indicated by return on asset and return on equity) andalso investors’ capital gain on shares. Value Added Intellectual Coefficient™ (VAIC™) introducedis used as proxy of firm’s effectiveness in managing its intellectual capital. Datawere drawn from 22 banking firms and 10 samples of publicly traded banking and insurancefirms respectively during 2005-2007. The linear multiple regression analysis suggests thatthe association between the efficiency of value added by a firm’s major resource bases and(1) return on asset, (2) return on equity, and (3) capital gain, are generally limited and insignificant.This is mainly due to the unique characteristics of banking companies comparedto other sectors. In contrast, for insurance sector confidently shows there is a significant associationbetween efficiency of VAIC™ toward financial profitability and investors’ capitalgain. This show that the power of intellectual capital is valuable information for related partiesin decision making and policy creation process especially in considering the growingsignificant role of banking and insurance companies in developing Indonesia economies.